Livestock Exchange hard seat 2011: Segenet Kelemu on Biosciences eastern and central Africa - Kelemu, Segenet (International Livestock Research Institute, 2011)
On 9 and 10 November 2011, the ILRI Board of Trustees held a 2-day 'liveSTOCK Exchange' to discuss and reflect on livestock research for development. The event synthesized sector and ILRI learning and helped frame future livestock research for development directions. During the meeting, Brian Perry interviewed Segenet Kelemu, Director of the Biosciences eastern and central Africa (BecA) Hub.